Outbreak of Eimeria kofoidi and E. legionensis coccidiosis in redlegged partridges (Alectoris rufa) - Maria Paola Tampieri; Fausto Marzadori; Elisabetta Raffini; Matteo Frasnelli; Mattia Cecchinato; Roberta Galuppi; Elena Catelli; Pier Giorgio Bolognesi (Italian Journal of Animal Science, 2010)
An outbreak of coccidiosis occurred in red-legged partridges is reported. At the post-mortem examination the birds showed a mucous haemorrhagic enteritis, mostly in the duodenal intestinal tract. Direct microscopic examination of intestinal content revealed the presence of a high number of oocysts. After incubation, on the basis of the morphological features, two species of coccidia were identified: Eimeria kofoidi and E. legionensis.